Sharia Rules and Controls for Publishing In Social Media - sobieel, Abdelmalek (Jordan Journal of Islamic Studies, 2023)
This research addressed the principles and legal guidelines for disseminating various content, whether in written form, images, or videos, through social media platforms. It also discussed the main purposes behind users’ intentions to publish content. The researcher reached several research findings and recommendations, including: Social media platforms exhibit both negative and positive behavioral aspects. Sharing judgments and stories is permissible as long as they do not involve forbidden actions. It is obligatory to distance oneself from those who spread vice or promote rumors. Neglecting their content and refraining from watching their broadcasts is key to minimizing their harm and diminishing their influence. Dissemination of scientific information is recommended when it is presented by a reliable expert. It is prohibited for non-experts to share content within their field of expertise if they lack confidence in it. If someone is not an expert and their credibility is in question, dislike is the least that can be done. Spreading rumors, even if they are true, that pertain to public affairs is not permissible. It is not permissible to share any post unless the user is reasonably confident in its accuracy. The use of social media platforms is subject to Sharia guidelines, which users must be aware of. The research also provided the following recommendations: Preachers and religious organizations should engage in inviting people and encouraging them not to follow individuals who produce harmful or weak content. Governments need to pay significant attention to social media as the “new media”, supporting it and allocating appropriate budgets to preserve Islamic and societal values and maintain identity. Implementing strict regulations to restrict the dissemination of content that harms individuals or entities, and more.